Effect of Technological Parameters on the AlSi12 Alloy Microstructure During Crystallization Under Pressure - Pastirčák R.; Ščury J.; Brůna M.; Bolibruchová D. (Archives of Foundry Engineering, 2017)
The paper deals with the impact of technological parameters on the heat transfer coefficient and microstructure in AlSi12 alloy using squeeze casting technology. The casting with crystallization under pressure was used, specifically direct squeeze casting method. The goal was to affect crystallization by pressure with a value 100 and 150 MPa. The pressure applied to the melt causes a significant increase of the coefficient of heat transfer between the melt and the mold. There is an increase in heat flow by approximately 50% and the heat transfer coefficient of up to 100-fold, depending on the casting conditions. The change in cooling rate influences the morphology of the silicon particles and intermetallic phases. A change of excluded needles to a rod-shaped geometry with significantly shorter length occurs when used gravity casting method. By using the pressure of 150 MPa during the crystallization process, in the structure can be observed an irregular silica particles, but the size does not exceed 25 microns.